Disturb the silence: presentation of deportation and political imprisonment in Lithuanian literature in 1956-1968 - Binkauskaitė, Gretė (Genocidas ir rezistencija, 2021)
The depiction of the crimes against humanity committed during the first (1940–1941) and second (1944–1953) Soviet occupations under Stalin’s rule in the form of deportations and imprisonment in the Gulag camps in prose works submitted to publishing institutions during the period under review.
Keywords: political prisoners; deportees; soviet literature; censorship